The effect of entrepreneurship orientation and flexibility toward adaptive innovation and improved firm performance - Rofiaty, Rofiaty; Aisjah, Siti; Susilowati, Christine (BISMA (Bisnis dan Manajemen), 2022)
This study analysed the effect of entrepreneurial orientation and flexibility on adaptive innovation and firm performance. The sample of this study consisted of 114 orchid business actors. The data analysis technique used in this study uses quantitative methods with the SEM analysis method (WarpPLS) as an analytical tool to process data. Data was collected by direct interview and through a Google Form. This study proves that entrepreneurial orientation directly and positively affects firm performance and adaptive innovation. Flexible management has a direct and positive effect on firm performance and adaptive innovation, while adaptive innovation has a positive effect on improving firm performance. On the other side, adaptive innovation has not a mediation role of entrepreneurship orientation toward firm performance, but adaptive innovation has a mediation role flexibility toward firm performance. The novelty of this study emphasize on the green economy run by orchid SMEs, that strives to enhance business performance through entrepreneurial orientation, adaptability, and adaptive innovation.